Myocardial ischemia as a cause of paroxysmal dyspnea in patients with stable coronary artery disease - S. F. Yarmedova; I. S. Yavelov; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Aim. To determine the potential of diagnosing myocardial ischemia as a cause of paroxysmal dyspnea in patients with stable coronary artery disease (CAD) before an in-depth examination.Material and methods. This cross-sectional single-center study included stable patients with an established diagnosis of CAD and complaints of paroxysmal dyspnea, who were undergoing inpatient treatment in the cardiology department (n=101). All study participants underwent treadmill stress echocardiography to detect transient myocardial ischemia. Complaints, anamnesis data, results of physical examination, laboratory tests, electrocardiography (ECG) and transthoracic cardiac ultrasound examination, including tissue Doppler were analyzed.Results. Myocardial ischemia according to stress echocardiography was detected in 36 (35,6%) patients. According to multivariate analysis, independent signs indicating myocardial ischemia as a cause of dyspnea were the duration of dyspnea attack (odds ratio (OR) 1,43, 95% confidence interval (CI): 1,06-1,92; p=0,02), typical angina (OR 5,57, 95% CI: 1,17-26,63; p=0,031), pathological Q wave (OR 6,66, 95% CI: 2,03-21,85; p=0,002), right atrium volume (OR 0,96, 95% CI: 0,92-1,00; p=0,045) and lateral e` (OR 1,26, 95% CI: 1,01-1,57; p=0,038). When combining these variables into a single regression equation, the area under the characteristic curve (ROC curve) was 0,83, 95% CI: 0,750,91; sensitivity, specificity, positive and negative predictive value for the optimal cutoff point were 88,9, 72,6, 57,1 and 91,1%, respectively. In turn, for the point scale created using these variables, the area under the ROC curve was 0,79 with 95% CI: 0,70-0,88; sensitivity, specificity, positive and negative predictive value were 83,3 and 64,6, 56,6 and 87,5%, respectively. There was no significant difference in the areas under the ROC curve for regression equation and point scale (p=0,355).Conclusion. The presence of myocardial ischemia as a cause of paroxysmal dyspnea in patients with stable CAD can be predicted based on the data available in real-world practice, including the characteristics of clinical manifestations, resting ECG, and transthoracic cardiac ultrasound.